PENGARUH IKLIM ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KUALITAS PELAYANAN - Endang Hermawan (DIALOGIKA, 2020)
This research is motivated by the low job satisfaction of employees which has an impact on service quality, aims to read and analyze: 1) organizational climate, career development, job satisfaction, and service quality in Cigasong District; 2) The magnitude of the influence of organizational climate on job satisfaction; 3) The magnitude of the influence of career development on job satisfaction; 4) The magnitude of the influence of organizational climate and career development on job satisfaction; and 5) The amount of influence of work on service quality. The research method used with survey techniques. Data collection using a questionnaire with a sample of 50 people who were determined by random sampling techniques. Data processing uses path analysis with the help of a SPSS computer program. The results of descriptive research are conducive organizational climate, transparent career development, satisfied employees, and good enough service quality; In terms of organizational climate and career development affect job satisfaction both partially and collectively, and job satisfaction affects the quality of service. Conclusion, both partially and jointly organizational climate and career development have an effect on job satisfaction and job satisfaction has an impact on service quality